2017
DOI: 10.3390/ijms18122581
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase RNF7 Negatively Regulates CARD14/CARMA2sh Signaling

Abstract: The three CARD-containing MAGUK (CARMA) proteins function as scaffolding molecules that regulate activation of the pro-inflammatory transcription factor NF-κB. Recently, mutations in CARMA2 have been linked to psoriasis susceptibility due to their acquired altered capacity to activate NF-κB. By means of two-hybrid screening with yeast, we identified RING finger protein 7 (RNF7) as an interactor of CARMA2. We present evidence that RNF7 functions as a negative regulator of the NF-κB-activating capacity of CARMA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The psoriasis-associated CARMA2 sh mutants Glu138Ala and Glu142Gly also escape the negative regulation exerted by two novel CARMA2 sh interactors identified by two-hybrid screening in yeast, namely the serine/threonine kinase Unc-51 Like Autophagy Activating Kinase 2 (ULK2) and the E3 ubiquitin ligase Ring Finger protein 7 (RNF7) ( 57 59 ). Both ULK2 and RNF7 are indeed able to repress CARMA2 sh -induced NF-κB activation, although through different mechanisms.…”
Section: Carma2 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The psoriasis-associated CARMA2 sh mutants Glu138Ala and Glu142Gly also escape the negative regulation exerted by two novel CARMA2 sh interactors identified by two-hybrid screening in yeast, namely the serine/threonine kinase Unc-51 Like Autophagy Activating Kinase 2 (ULK2) and the E3 ubiquitin ligase Ring Finger protein 7 (RNF7) ( 57 59 ). Both ULK2 and RNF7 are indeed able to repress CARMA2 sh -induced NF-κB activation, although through different mechanisms.…”
Section: Carma2 Signalingmentioning
confidence: 99%
“…Both ULK2 and RNF7 are indeed able to repress CARMA2 sh -induced NF-κB activation, although through different mechanisms. In particular, ULK2 phosphorylates CARMA2 sh and promotes lysosomal degradation of BCL10, whereas RNF7 alters the ubiquitination state of MALT1 and NEMO ( 58 , 59 ). Intriguingly, a protein similar to RNF7, named RNF181, has been identified as an interactor of CARMA1 and functions as an E3 ubiquitin ligase to inhibit antigen receptor signaling to NF-κB downstream of CARMA1 ( 60 ).…”
Section: Carma2 Signalingmentioning
confidence: 99%
“…BCL10 filaments allow MALT1 oligomerization and activation, which eventually ensues in recruitment of the IKK complex and NF-κB activation [ 1 , 2 , 3 , 4 , 12 ]. In addition to the component of the CBM complex, and similarly to other CARMA proteins, CARMA2 sh function is modulated by a number of CARMA2 sh -interacting proteins [ 13 , 14 , 15 ] and by the de-ubiquitinase A20 [ 8 ]. We have also recently shown that CARMA2sh and the adapter protein TANK are required to activate the NF-κB response following exposure to poly (I:C), an agonist of Toll-like Receptor 3 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These filaments allow MALT1 oligomerization and activation which eventually results in recruitment of the I-kappa-B-kinase (IKK) complex and the consequent NF-κB activation (Blonska & Lin, 2011;Jiang & Lin, 2012;Jiang et al, 2016;Lu et al, 2018;Qiao et al, 2013;Scudiero et al, 2014;Stilo et al, 2004). In addition to the component of the CBM complex, the NF-κBinducing activity of CARMA2 also requires the adapter molecule TRAF2 (Scudiero et al, 2011), and, similarly to other CARMA proteins, is modulated by a number of CARMA2-interacting proteins, including the serine/threonine kinase Unc-51 like autophagy activating kinase 2 (Scudiero et al, 2017), the DEP domain-containing protein DEPDC7 (D' Andrea et al, 2014), the de-ubiquitinase A20 (Scudiero et al, 2011;Stilo, Varricchio, Liguoro, Leonardi, & Vito, 2008), and the E3 ubiquitin ligase Ring Finger protein 7 (Telesio et al, 2017). Thus, the study of molecules capable of modulating the NF-κB-inducing property of CARMA2 is particularly important, as they represent potential therapeutic targets for the treatment of inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 99%